Performance analysis of LDPC decoding algorithm based on PPM modulation for UWOC system under turbulent channel - Ji, Feng; Wang, Da-Shuai; Wang, Le; Tong, Shou-Feng (Optical review (Tokyo, Japan), 2025)
Turbulence effect is an important factor leading to performance degradation of underwater wireless optical communication (UWOC) systems. In order to improve the reliability of the communication system, this paper adopts a UWOC system based on low-density parity-check (LDPC) code and pulse position modulation (PPM) to overcome the effects caused by turbulence, and proposes an improved Offset Min-Sum algorithm to combat turbulent channel interference. The generalized gamma distribution (GGD) distribution is used as the channel model, and the relationship between BER, SNR, different of LDPC decoding algorithms, and PPM order is quantified by simulation for different turbulence intensities.The results show that the performance of the improved OMS algorithm is optimal under weak, moderate, and strong turbulence; at σ I 2 =2.0399 and BER = 10 –6 , the improved OMS algorithm with 4-PPM, 8-PPM, and 16-PPM modulation has a coding gain of 0.16 dB, 1.2 dB, and 4 dB, respectively, compared with the OMS algorithm.